THE ROLE OF PHYSICAL EXERCISES IN TRAINING YOUNG VOLLEYBALL PLAYERS - Djanxodjayev Nurlan Djanizakovich (Web of Journals Publishing, 2023)
The article describes the specific importance of systematic physical training of volleyball players from the age of 10-12 and the results of scientific research on establishing a systematic approach to conducting general and special physical training.
Keywords: Physical training, physical qualities, exercises, system, training, stage, means, methods.